PENGARUH PROMOSI DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK BIORE MEN DI KOTA SEMARANG - Kautsar Ghaniyu Rakhman; Hari Susanta Nugraha (Universitas Diponegoro, 2016)
This study is on the influence of promotion and product quality product purchase decision against Biore Men In Semarang. The objective of this study was to determine the effect of promotion and quality of products on purchase decision either partially or simultaneously. This type of research is explanatory research. The population in this study is a consumer productusers Biore men in the city of Semarang. Pursposive sampling technique using sampling with asample size of 100 people. Methods of data collection using questionnaires, while engineering analysis using multiple regression analysis. Calculations in this study using SPSS for windows. The calculations show that there are significant promotions and product quality both on productpurchasing decisions Biore Men in Semarang. Advice given is the consumer should pay attention to the promotion of Men Biore products through various advertising media that determine the development. Consumers should pay attention to the quality so they know when the product has quality products that are low or high.